Planejamento estratégico: loja Peça Rara, Não-Me-Toque/RS - Silva, Mônica Jandrey da (2022)
The present study aimed to identify the strengths and weaknesses of Loja Peça Rara, as well as the threats and opportunities of the company's external environment and to propose, from the diagnosis carried out, strategies aimed at increasing the company's competitiveness. In accordance with this, semi-structured interviews were carried out with the owners in order to better understand the company's structure and collect data for the implementation of the action plan. Afterwards, interviews were carried out with the company's employees, in order to complement the organization's internal diagnosis. Questionnaires were also carried out with the company's customers, who were chosen through a non-probabilistic convenience sampling, seeking to identify their perceptions regarding the store's strengths and weaknesses, as well as suggestions. To analyze the external environment, information was sought in primary and secondary data. When analyzing the internal and external variables of the company through the SWOT Matrix, a predominance of strengths in the internal environment and opportunities in the external environment was evidenced, classifying the company in a strategic development posture. Subsequently, a 5W2H action plan was created, in order to remedy the weaknesses presented by the company, such as the deficiency in digital marketing and local dissemination, need for electronic devices for sales development, lack of a means of2 payment for the store and investment in employee sales training, thus preparing the organization to face the highly competitive market, taking advantage of opportunities and minimizing threats. The results obtained from the research and analysis of the environment demonstrate that the company has great potential to achieve its objectives, through strategic planning and its action plan.